2021
DOI: 10.33394/bjib.v9i1.3703
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Video Pembelajaran melalui Zenius.Net terhadap Hasil Belajar Kognitif Biologi Siswa Madrasah Aliyah Kelas X dan XI

Abstract: The use of media in the learning process can generate motivation and stimulus in learning activities, and even bring psychological effects on students. The purpose of this study was to determine the effect of learning videos through Zenius.Net on cognitive biology learning outcomes for students of Madrasah Aliyah class X and XI. The type of research used is descriptive quantitative, which was carried out with a pre-experimental research method using a one group pretest posttest research design. The research sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
2
0
1
Order By: Relevance
“…zenius.net-based learning videos can improve students' cognitive learning outcomes. This is in accordance with research by Safitri, et al, (2021), stating that the use of learning videos through Zenius.Net significantly improves students' biological assessments in the cognitive domain. In line with research (Safitri, Pahriah, &;Fuaddunnazmi, 2022) concluded that the application of zenius.net-based learning videos is effective in increasing students' understanding of chemistry concepts.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…zenius.net-based learning videos can improve students' cognitive learning outcomes. This is in accordance with research by Safitri, et al, (2021), stating that the use of learning videos through Zenius.Net significantly improves students' biological assessments in the cognitive domain. In line with research (Safitri, Pahriah, &;Fuaddunnazmi, 2022) concluded that the application of zenius.net-based learning videos is effective in increasing students' understanding of chemistry concepts.…”
Section: Resultssupporting
confidence: 92%
“…This suggests that, zenius.net-based learning videos can have an effect on cognitive learning outcomes of students' chemical properties, as shown in Figure 2 below. According to Safitri, et al (2021), the results of data analysis that have been carried out have obtained a pretest value of 34.4, while a posttest value of 78.6. These results showed that there was an increase in student cognitive learning outcomes (gain) by 44.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut peneliti video pembelajaran melalui Zenius.Net dapat meningkatkan hasil belajar kognitif biologi siswa. Video merupakan salah satu media pembelajaran yang dapat digunakan untuk memotivasi siswa, dan sekaligus dapat meningkatkan hasil belajar kognitif siswa (Safitri, 2021).…”
Section: Metodeunclassified